Association of brain-derived neurotrophic factor DNA methylation and reduced white matter integrity in the anterior corona radiata in major depression - Choi, Sunyoung; Han, Kyu-Man; Won, Eunsoo; Yoon, Bong-June; Lee, Min-Soo; Ham, Byung-Joo (Journal of affective disorders, 2015)
Considerable evidence suggests a crucial role for the epigenetic regulation of brain-derived neurotrophic factor (BDNF) in the pathophysiology of major depressive disorder (MDD). However, the relationship between BDNF DNA methylation and white matter (WM) integrity in MDD has not yet been investigated. In the current study, we examined the association between the DNA methylation status of the BDNF promoter region and WM integrity in MDD. Sixty patients with MDD and 53 healthy controls underwent T1-weighted structural magnetic resonance imaging (MRI), including diffusion tensor imaging (DTI), to assess their WM integrity. BDNF DNA methylation at 4 CpG sites of the promoter region was also measured. As compared to healthy controls, the MDD group demonstrated reduced fractional anisotropy (FA) in the bilateral anterior and posterior corona radiata (ACR and PCR), genu of the corpus callosum, and the bilateral posterior thalamic radiations. We observed a significant inverse correlation between the DNA methylation of the BDNF promoter region and the FA of the right ACR in MDD patients. Our findings demonstrate a relationship between methylation of the BDNF promoter region and the integrity of the ACR, a key structural component of the emotional and cognitive control network involved in the pathophysiology of MDD. This correlation suggests that BDNF DNA methylation may contribute to structural WM changes in MDD patients.